Effect of sex and final fattening on ultrasound and carcass traits in Iberian pigs. - Ayuso, D; González, a; Hernández, F; Peña, F; Izquierdo, M (Meat science, 2014)
A hundred and twenty-five castrated Iberian pigs (61 males and 64 females, from 106.9 kg of live weight at star to 160.3 kg at slaughter) was used to investigate the effect of feeding system on carcass attributes (backfat thickness and loin area measured with ultrasound before slaughter, and intramuscular fat and weights and yields of hams, forelegs and loins after slaughter). Pigs were fattened outdoor under extensive conditions. There were 4 treatments: "montanera", M; "recebo", R; "cebo a campo", C; and high oleic fed, O). Ultrasound images were collected at two rib locations (10th and 14th). M and O groups had the highest fat thickness and loin area was lower in M than in C group. M and O showed higher carcass weight and yield than the other groups. The largest ham weight was for C and the lowest for M groups. Loin weight and yield were higher in M and R than the other two groups (O and C).
Keywords: Adipose Tissue; Adipose Tissue: chemistry; Adipose Tissue: ultrasonography; Animal Feed; Animal Feed: analysis; Animals; Body Weight; fatty acids; Fatty Acids: analysis; Female; Image Processing, Computer-Assisted; Male; meat; Meat: analysis; Muscle, Skeletal; Muscle, Skeletal: chemistry; Muscle, Skeletal: ultrasonography; Phenotype; Sex Factors; Swine

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 16921928
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain

Fatty acid composition of abdominal adipose tissue in broilers fed green-oak (Quercus ilex), cork oak acorn (Quercus Suber L.) based diets - Bouderoua, Kaddour; Selselet-Attou, Ghalem (Anim. Res., 2003)
Male broilers, 30 for every diet, were fed for six weeks, diets containing 60% green oak (GO) and oak cork (CO) acorns compared to 60% corn (C). The body weight of the chickens fed the oak acorn-based diets was 25% lower than that of the controls (C). Abdominal adipose tissue (AAT) was twice heavier in the controls compared to broilers fed oak acorn-based diets. The total lipids of AAT were higher in the controls compared to the oak acorn fed chickens (34.4 against 15.3 g per 100 g of AAT in the CO). The palmitic and oleic acid proportions were comparable in the AAT of chickens fed with the different diets. The proportion of linoleic acid, obtained exclusively by the diets, was significantly higher in the chickens fed oak acorn-based diets (23%), compared to the controls (19%). Reciprocally, palmitoleic acid was present in a small proportion in chickens fed oak acorns (4 to 5%). The observed variation of the fatty acid content of abdominal fat of acorn-fed chickens requires further research on the precise nutrient digestibility of oak acorns before considering them as a potential feed.
Keywords: Adipose Tissue; broilers; Lipids; lipogenesis; oak acorn

Fatty acid composition of abdominal adipose tissue in broilers fed green-oak (Quercus ilex), cork oak acorn (Quercus Suber L.) based diets - Bouderoua, Kaddour; Selselet-Attou, Ghalem (Anim. Res., 2003)
Male broilers, 30 for every diet, were fed for six weeks, diets containing 60% green oak (GO) and oak cork (CO) acorns compared to 60% corn (C). The body weight of the chickens fed the oak acorn-based diets was 25% lower than that of the controls (C). Abdominal adipose tissue (AAT) was twice heavier in the controls compared to broilers fed oak acorn-based diets. The total lipids of AAT were higher in the controls compared to the oak acorn fed chickens (34.4 against 15.3 g per 100 g of AAT in the CO). The palmitic and oleic acid proportions were comparable in the AAT of chickens fed with the different diets. The proportion of linoleic acid, obtained exclusively by the diets, was significantly higher in the chickens fed oak acorn-based diets (23%), compared to the controls (19%). Reciprocally, palmitoleic acid was present in a small proportion in chickens fed oak acorns (4 to 5%). The observed variation of the fatty acid content of abdominal fat of acorn-fed chickens requires further research on the precise nutrient digestibility of oak acorns before considering them as a potential feed.
Keywords: Adipose Tissue; broilers; Lipids; lipogenesis; oak acorn